2022
DOI: 10.1042/cs20220083
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 nicotinic acetylcholine receptor mediates chronic nicotine inhalation-induced cardiopulmonary dysfunction

Abstract: Cigarette smoking remains the leading modifiable risk factor for cardiopulmonary diseases; however, the effects of nicotine alone on cardiopulmonary function remain largely unknown. Previously, we have shown that chronic nicotine vapor inhalation in mice leads to the development of pulmonary hypertension (PH) with right ventricular (RV) remodeling. This study aims to further examine the cardiopulmonary effects of nicotine and the role of the α7 nicotinic acetylcholine receptor (α7-nAChR), which is widely expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Furthermore, the impact of nicotine exposure on the cardiovascular system is complex, as its direct effects differ according to cell type. Previous studies identified multiple nAChR alpha-subunits in rat arteries (47,48) and there is strong evidence that nicotine exerts deleterious effects on the vasculature through its interaction with nAChRs (49), being α7 nAChRs a key player in these processes (50). These results are in line with previous studies in which α7 nAChR is the transducer receptor for nicotinic signaling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the impact of nicotine exposure on the cardiovascular system is complex, as its direct effects differ according to cell type. Previous studies identified multiple nAChR alpha-subunits in rat arteries (47,48) and there is strong evidence that nicotine exerts deleterious effects on the vasculature through its interaction with nAChRs (49), being α7 nAChRs a key player in these processes (50). These results are in line with previous studies in which α7 nAChR is the transducer receptor for nicotinic signaling.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, previous studies have shown that nicotine induces reorganization of cytoskeletal structures in vascular SMC, including changes in α-actin, vimentin, and β-tubulin, and vascular dysfunction. These have been shown to be at least partially mediated by the α7 nAChR (51,52,53). On the other hand, α7 nAChR exhibits high permeability to calcium, enough to couple the activity of this receptor to intracellular calcium signaling pathways (54).…”
Section: Discussionmentioning
confidence: 99%
“…These changes are abrogated by treatment with losartan, a specific AT 1 R antagonist ( 33 ). Nicotine-induced pulmonary hypertension, RV remodeling, and vascular dysfunction are ameliorated by α7 nicotinic cholinergic receptor knockout, and are absent in female mice ( 58 ). The pathogenesis of pulmonary hypertension induced by Sugen and hypoxia also involves α7 nicotinic cholinergic receptor-mediated cross-talk between cardiomyocytes and cardiac fibroblasts, leading to RV fibrosis ( 60 ).…”
Section: Methodsmentioning
confidence: 99%